Kritik Konten Israiliyyat Dalam Tafsir Dan Hadis: Analisis Riwayat Dan Dirayat - Muhammad Sholihin; M. Basyir Faiz Maimun Sholeh; Imam Sahal Ramdhani; Moh Sholihin (STAI Nurul Qadim, 2025)
Israiliyyat are often used to provide additional details to narratives in the Qur'an and Hadith. However, the presence of fabricated Hadiths and questionable Israiliyyat has sparked debate among scholars. This study aims to analyze the criticism of Israiliyyat content using both riwayah (transmission-based) and dirayah (content-based) approaches, with a particular focus on the contributions of Abu Syahbah, a prominent Hadith scholar. Abu Syahbah is known for his critical stance toward Israiliyyat and fabricated Hadiths, especially in the context of fifteen major Tafsir (Qur'anic exegesis) works. This research employs a qualitative descriptive method through a literature review, examining Israiliyyat narratives by validating their chains of transmission (sanad) and texts (matan), as well as assessing their alignment with Islamic teachings. The findings reveal that Abu Syahbah rigorously verifies the sanad and matan of each narrative to ensure their integrity and reliability, and he also critiques scholars or exegetes who rely on Israiliyyat without sufficient verification. Challenges in this critique include the complexity of lengthy transmission chains and the questionable credibility of certain narrators. The dirayah analysis is also applied to evaluate the narratives in light of fundamental Islamic principles, historical context, and socio-cultural background. This study affirms the importance of combining riwayah and dirayah analysis in safeguarding the purity of Islamic teachings from unauthentic narratives.